2015
DOI: 10.1186/s12302-014-0036-z
|View full text |Cite|
|
Sign up to set email alerts
|

Bioaccumulation in aquatic systems: methodological approaches, monitoring and assessment

Abstract: Bioaccumulation, the accumulation of a chemical in an organism relative to its level in the ambient medium, is of major environmental concern. Thus, monitoring chemical concentrations in biota are widely and increasingly used for assessing the chemical status of aquatic ecosystems. In this paper, various scientific and regulatory aspects of bioaccumulation in aquatic systems and the relevant critical issues are discussed. Monitoring chemical concentrations in biota can be used for compliance checking with regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Our study indicates that microcystins can be bioaccumulated in mussels, a finding that is in accordance with the literature [ 42 46 ]. The fact that mussels are filter feeders, enables them to bioaccumulate environmental pollutants [ 47 ], like microcystins [ 48 ]. A study in the brackish waters of Curonian lagoon [ 49 ] in Lithuania, revealed that mussels Dreissena polymorpha (zebra mussels), accumulated microcystins at high concentrations, up to 139 ng g −1 dry weight analyzed by ELISA and 284 ng g − dry weight by PPIA.…”
Section: Discussionmentioning
confidence: 99%
“…Our study indicates that microcystins can be bioaccumulated in mussels, a finding that is in accordance with the literature [ 42 46 ]. The fact that mussels are filter feeders, enables them to bioaccumulate environmental pollutants [ 47 ], like microcystins [ 48 ]. A study in the brackish waters of Curonian lagoon [ 49 ] in Lithuania, revealed that mussels Dreissena polymorpha (zebra mussels), accumulated microcystins at high concentrations, up to 139 ng g −1 dry weight analyzed by ELISA and 284 ng g − dry weight by PPIA.…”
Section: Discussionmentioning
confidence: 99%
“…PPARs have a pivotal role in regulating metabolism, resulting the primary lipid sensors in vertebrates and being highly conserved between humans and zebrafish ( 17 ). Poly and mono unsaturated fatty acids (FA), eicosanoids and lipophilic hormones are PPAR natural ligands ( 18 ) with different affinity to PPAR isoforms and induce the expression of genes and enzymes involved in lipid metabolism.…”
Section: Potential Mechanisms By Which Edcs Exert Their Effectsmentioning
confidence: 99%
“…Measuring bioaccumulation through the experimental determination of a bioaccumulation factor (BAF), bioconcentration factor (BCF), or biomagnification factor (BMF) is often challenging because it depends on many abiotic (such as water pH, salinity, and concentration of organic compounds) and biotic factors (such as lipid content, age, and/or sex of an organism; Glenn and Klaine 2013;Sch€ afer et al 2015). When there are no experimentally determined BAF, BCF, or BMF values, the partitioning of a chemical between aqueous and organic phases is often used as a surrogate measure of its bioaccumulation potential.…”
Section: Introductionmentioning
confidence: 99%